Evolution of Traditional Water Collection Techniques in the Algerian Sahara - HAMDAOUI, Tahar Medjdoub; REMINI, Boualem (GeoScience Engineering, 2020)
This article discusses many of the inherited techniques for collecting and managing spring water used in the gardens of Boussaada, Ain Madhi, Small Mechria, and Stitten located in the Saharan atlas’ ranges over a period of nine centuries. Based on the missions carried out since 2017 in the four regions, we conducted site investigations and surveys of the local population. The results showed that domestic water supply and irrigation were carried out using traditional water collecting techniques such as well and foggara and small dams. The water harvesting technology characterizes a specific region according to its topography and hydrology. Currently, this hydraulic heritage meets technical and social problems, especially with the advent of modern technologies that give more water with less human effort but hurt the environment. The objective of this study is to conduct a comprehensive inventory of all water sources in the study areas while evaluating the negative impact on them due to the emergence of modern technologies. Keywords: Algeria; Dam; Foggara, Oasis; Source; Valley. DOI 10.35180/gse-2020-0045